Single-Cell Virology: On-Chip Investigation of Viral Infection Dynamics - Guo, Feng; Li, Sixing; Caglar, Mehmet Umut; Mao, Zhangming; Liu, Wu; Woodman, Andrew; Arnold, Jamie J.; Wilke, Claus O.; Huang, Tony Jun; Cameron, Craig E. (Cell reports (Cambridge), 2017)
We have developed a high-throughput, microfluidics-based platform to perform kinetic analysis of viral infections in individual cells. We have analyzed thousands of individual poliovirus infections while varying experimental parameters, including multiplicity of infection, cell cycle, viral genotype, and presence of a drug. We make several unexpected observations masked by population-based experiments: (1) viral and cellular factors contribute uniquely and independently to viral infection kinetics; (2) cellular factors cause wide variation in replication start times; and (3) infections frequently begin later and replication occurs faster than predicted by population measurements. We show that mutational load impairs interaction of the viral population with the host, delaying replication start times and explaining the attenuated phenotype of a mutator virus. We show that an antiviral drug can selectively extinguish the most-fit members of the viral population. Single-cell virology facilitates discovery and characterization of virulence determinants and elucidation of mechanisms of drug action eluded by population methods. [Display omitted] •High-throughput on-chip culturing and live-cell imaging of single, infected cells•Single-cell, temporal infection dynamics revealed bias of population averaging•Cells refractory to lysis exposed; infection thereof may lead to viral persistence•An antiviral agent was shown to target only a subset of the viral population Guo et al. use a microfluidics device installed on a fluorescence microscope to monitor the kinetics of viral infection in single cells. Between-cell variation in outcomes of infection exists at all phases of the life cycle. Cellular gene expression governs the eclipse phase; viral genetics govern replication rate and yield.